How can the World Stroke Organization (WSO) optimize education in stroke medicine around the world? Report of the 2018 WSO Global Stroke Stakeholder Workshop. Issue 8 (October 2019) - Gubitz, Gord; Saini, Monica; Belson, Sarah; Sahathevan, Ramesh; Sandercock, Peter
Background: Education in stroke is relevant to stroke survivors, clinicians, care providers, and healthcare system administrators and is of special importance in resource-limited settings. The World Stroke Organization Education Committee undertook a program of work, culminating in a focused workshop, to establish the key educational priorities, and work toward maximizing the WSOs impact on the global burden of stroke. Methods: A facilitated workshop took place during the World Stroke Congress in Montreal, Canada in October 2018. The workshop was developed using opinions on priority topics for World Stroke Organization educational activities obtained from web-based surveys of World Stroke Organization Members, supplemented by interviews with international stroke support organizations. The workshop included over 50 international participants, selected to represent a balance of age, gender, geographical region, and different levels of health resources. Participants also included members of the World Stroke Organization Education Committee, the World Stroke Academy, stroke support organizations, and the International Journal of Stroke editorial board. The workshop focused on understanding more about educational needs (at all levels), with emphasis on resource-limited settings. Three broad questions were posed: (1) What are the key educational needs: (a) in your region, (b) from your perspective (e.g. stroke support organization)? (2) Do the current educational activities offered by World Stroke Organization and WSA meet your needs? (3) What could World Stroke Organization/World Stroke Academy offer in your region that would meet your needs? The facilitated discussions were recorded, and the results transcribed and summarized by members of the World Stroke Organization Education Committee. Results: Five key needs were identified: 1. Collaborative interdisciplinary, training in both stroke care and how to advocate for stroke. 2. Educational materials provided in a wider range of formats that could be adapted to local circumstances and clinical practices. 3. Educational activities for healthcare providers and stroke support organizations organized regionally, with the World Stroke Organization providing organizational support, and a pool of experts, therapists, nurses, etc. to deliver locally relevant materials. 4. Clear and authoritative online resources, where it is easy to find key policy and protocol guidance. 5. A range of online interactive education and training resources to help build knowledge and competence in stroke care. Conclusion: The results of the workshop have been presented to the World Stroke Organization Board and will be used to help to guide the educational initiatives of the World Stroke Organization and World Stroke Academy going forward.